Konsep Dasar Produktifitas Tenaga Kerja dalam Perspektif Ekonomi Islam - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The spirit in work illustrates the aspects of good work ethics in humans, sourced from the quality of self, realized based on the value of the work ethic that is implemented in work activities. Islamic teachings strongly encourage his people to work hard, and that the teachings of Islam contain the spirit and encouragement of the growth of culture and labor productivity activities that have a balanced spiritual dimension. The work ethic in Islam is closely linked to the values contained in the Qur'an and the Sunnah about